Valorization of AZ91 by the hydrolysis reaction for hydrogen production (Electrochemical approach) - S. Al Bacha; I. Aubert; M. Zakhour; M. Nakhl; J.L. Bobet (Journal of Magnesium and Alloys, 2021)
The hydrolysis of Mg-based materials appears to be an ideal solution for clean energy production. Green hydrogen was produced by the hydrolysis reaction of a “standard” AZ91 alloy (called AZ91 in the following) in “model” seawater solution. Two milling speeds (i.e. 250 rpm and 350 rpm) were tested to enhance the reactivity of AZ91. Graphite and AlCl3 were used as ball milling additives. Milling at higher rotational speed is more energetic, hence it ameliorates the most the hydrolysis performance of AZ91. Comparing both milling additives, AlCl3 enhances the most the hydrolysis of AZ91 with a generation of 65% of its theoretical H2 generation capacity. The best material was obtained by milling AZ91 at 350 rpm with graphite for 2 h followed by a further milling with AlCl3 for 2 h – a yield of 75% of its theoretical H2 generation capacity was reached within a few minutes. The corrosion behavior of milled AZ91 was investigated by anodic polarization and electrochemical impedance spectroscopy (EIS). The calculated electrochemical parameters from EIS fitting of two materials milled under different conditions but with the same milling additive are approximately the same. This suggests that, in order to fully evaluate the reactivity of AZ91, hydrolysis, anodic polarization and EIS must be considered.